KAJIAN BIOREMEDIASI PADA TANAH TERCEMAR PESTISIDA - Dwi Juli Puspitasari; Kahiruddin Khairuddin (KOVALEN: Jurnal Riset Kimia, 2016)
The use of pesticides to eradicate pests are an integral part in farming system. Pesticides use  to increase production and protect the production of physical defects can also cause pollution on agricultural land. The presence of pesticide residues in soil and agricultural production can cause health problems for human and animals  and even death. To overcome this problem there needs a way to degrade hazardous waste in the  environment by performing the remediation. Remediation is carried out by microorganisms fungi, bacteria and algae known as bioremediation. Bioremediation aims to transform compounds into harmless compounds with the end result are  carbon dioxide, water and biomass cells. The advantages of bioremediation are  environmentally friendly, highly efficient, low cost, can be implemented directly in the field, laboratory and combined with chemical and physical methods.Keywords: bioremediation, soil degradation, pesticides, microorganisms